Synthesis ZnO/RGO nanocomposite: Structural characteristics and antifungal/antibacterial properties - Mahshid Chireh; Mahmoud Naseri; Maryam Rahimi; Ali Reza Solymani (Progress in Physics of Applied Materials)
The research presented herein involves the synthesis of ZnO nanoparticles (NPs) via a simple thermal treatment approach, utilizing a solution comprising Polyvinylpyrrolidone (PVP) as capping reagent and Zn nitrate as the metal source. Subsequently, these ZnO NPs underwent a conversion process into a ZnO/RGO nanocomposite (NCs) through a simple process of polymerization. Various characterization techniques such as Fourier transform infrared spectroscopy, field emission scanning electron microscopy and X-ray diffraction, were employed to investigate the phase composition, microstructure form, and degree of crystallinity. At room temperature, Analysis using Energy dispersive X-ray analysis confirmed the presence of C, Zn, and O elements in the prepared nanocomposite composition. Surface area of the ZnO/RGO NCs was determined through the adsorption–desorption isotherms of N2 gas using Brunauer–Emmett–Teller analysis. The antibacterial and antifungal activities of graphene, ZnO, and ZnO/RGO NCs with results from the disc agar diffusion method indicating the absence of antibacterial activity in graphene and ZnO NPs, while the ZnO/RGO nanocomposites displayed notable antifungal activity. Moreover, graphene alone did not exhibit any noticeable antifungal properties.